Toxicological Analysis of Exhumed Specimens: A Challenge for Toxicologists - Muhammad Taimoor Chaudhary; Sardar Ali Wattoo; Muhammad Zar Ashiq; Saima Afzal; Mohammad Sarwar; Mohammad Ashraf Tahir (Arab Journal of Forensic Sciences & Forensic Medicine, 2016)
The objective of this work is to describe the type of biological samples submitted for toxicological analysis after exhumation. Forensic toxicologists receive a variety of biological samples, but exhumed biological specimens with varying degrees of putrefaction pose a greater challenge for analysis. Usually, immunoassay and colorimetric screening are the first line approach for toxicological analysis. Suitable samples can be selected for direct analysis using chromatographic techniques with a mass spectrometer, providing reliable results. The authors report two case studies where exhumed specimens were submitted for the determination of possible intoxication. The deceased were severely injured and remained hospitalized for more than 24 hours before death. Their corpses were exhumed for chemical analysis. For the toxicological analysis, selected samples were analyzed by immunoassay and a gas chromatograph mass spectrometer (GC/MS) with electron impact ionization. Although the samples were negative for drugs of abuse (benzodiazepines and opiates), by immunoassay, midazolam (benzodiazepine) was detected in putrefied material using GC/MS, thus indicating the hospitalization before death.